Incentive system and motivation of employees to scientific activity: economic aspects at the university and state level - A.E. Artyukhov; T.A. Vasylieva; I.I.Volk; S.V. Lyeonov (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2021)
The algorithm of stimulation to scientific activity at local and state levels is formed in the paper. The review of research on incentives for employees in the world scientific practice is carried out, the connection between incentives and innovations resulting from scientific activity is demonstrated. The issues of academic motivation, a component of which is motivation for scientific activity, as well as barriers to motivation for the exchange of scientific data, which is especially relevant in the scientific environment, which is on the path of transition to open science, are discussed. The distinction between the concepts of stimulation and motivation in the context of encouragement to perform scientific tasks is presented. The problem of lack of practice of using tools of motivation for scientific activity at the state level is outlined. The categories of sources of stimulation of scientific activity in Ukraine are given and the actual problems of involvement of categories of stimulation are investigated. The ways of solving the problem of funding at the university level, available within the lowest categories of sources of stimulation of research projects, are analyzed. The connection of economic indicators of scientific activity evaluation with the requirements of actual competitions for obtaining scientific research funding is demonstrated. Problems of management and implementation of scientific projects related to the Pareto principle and the Ringelman effect are discussed. The prerequisites for improving the quality of group work in a research project is proposed. To determine the points of influence for the implementation of the proposed prerequisites are diagrams of the state of work on research projects and publication activities within research groups. The successful experience of Sumy State University in stimulating the effectiveness of scientific activity and the method of determining the rating of structural units, which determines the indicators of influence on the level of evaluation of scientific results, are demonstrated.